Intuitive content management system via manipulation and duplication with if-else rules classification - Chan, Chung Hoong (2018)
A Content Management System (CMS) is a system that is used to control or manage content on a website such as text, links, image, HTML documents, and other forms of media. The fact that CMS is dynamically generated is a problem on pages loading speed which is currently used in Drupal, Joomla, WordPress, and Agility CMS. However, static websites load faster than dynamic ones, since the content is delivered as-is and can be cached by a content delivery network (CDN), and the web server does not need to perform any application logic or database queries. In order to solve this problem, an Intuitive Content Management System (ICMS) is proposed in this study. The aim of ICMS is to help non-technical users to design their website easily. Users will need to choose the content from templates, upload images directly, and fill in necessary documents to create a quick, easy, and static website which can reduce load time from dynamic website. An ICMS is a content management system that uses three main important techniques to build, such as Manipulation method, Data Mining Prediction, and Boyer-Moore Horspool algorithm. The manipulation method is a method that can easily generate a website and store the information precisely in a correct order with buffering method. A buffering method will be implemented after the generation of website, in order to transform dynamic website into static website. Therefore, a static website is created which load faster than dynamic website. An ICMS needs to use data mining classification to accurately classify stored data while predicting the user’s database information to give the best preferences and suitable template chosen for an end user to select. The time consumed for choosing a template will decrease as an example of giving the user 5 templates to choose from out of 100. As a result, it can minimize the workload of choosing a template and the time consumed which come from preferences of 5 recommendation which are 20 times faster than before. Boyer-Moore Horspool algorithm is adapted in ICMS which is mainly for faster searching result. As a result, ICMS can transform dynamic websites into static websites with faster load speed using manipulation method mixed with data mining classification prediction and Boyer-Moore Horspool algorithm which can be classified, edited, adjustable and searched more precisely. An ICMS makes things easy for any small business or personal business to create, manage, and publish interactive observations to interpret their own websites, which also support mobile platform browsers.